PINS: 20 YEARS OF OPPOSITIONAL AND CRITICAL PSYCHOLOGY - Hayes, Grahame (PINS-Psychology in Society, 2026)
Anniversaries are strange and arbitrary markers of time, and yet are universally "celebrated". The remembrance of things past can be the occasion for joyous celebration as well as for sorrowful remembering. 2004 marks 10 years of democracy in South Africa, and besides being an election year, will be the occasion of numerous analyses of post-apartheid society in its first decade as well as an assessment of the performance of the ANC government over this period. So decades become the most common time-span for commentary, critical reflection, and celebration.